The Effect of Slow Stroke Back Massage on Headache Intensity in Hypertensive Older Adults - Sang Ayu Ketut Candrawati; Ni Komang Sukra Andini; Desak Made Ari Dwijayanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: A Headache is a common complaint among individuals with hypertension and is often associated with elevated blood pressure. One form of complementary therapy that can be applied to alleviate this symptom is Slow Stroke Back Massage (SSBM). Objectives: This study aimed to examine the effect of Slow Stroke Back Massage on headache intensity in older adults with hypertension. Methods: This quantitative research employed a quasi-experimental design with a non-equivalent control group pretest-posttest approach. Thirty-four hypertensive older adults participated in the study and were selected through purposive sampling. The intervention group received SSBM therapy three times per week for 10 minutes over four weeks, while the control group received only standard antihypertensive medication. Headache intensity was measured using the Numeric Rating Scale (NRS). Results: The mean pre-test headache intensity score was 6.12 ± 1.62 in the intervention group and 5.82 ± 1.55 in the control group. After the intervention, the mean scores decreased to 2.71 ± 1.53 and 3.82 ± 1.55, respectively. The reduction in headache intensity was 3.41 points in the intervention group and 2.00 points in the control group. The Wilcoxon test showed a significant difference in the intervention group (p = 0.000), while the paired sample t-test confirmed significance in the control group (p = 0.000). The pre-test comparison between groups using the independent t-test indicated no significant difference (p = 0.592), whereas the post-test comparison using the Mann-Whitney U test showed a significant difference (p = 0.041). These findings suggest that SSBM significantly reduces headache intensity among hypertensive older adults. Conclusions: Slow Stroke Back Massage is an effective, safe, and non-pharmacological intervention for reducing headache intensity in hypertensive patients. Its application is recommended as a complementary therapy in elderly care.